Fatigue and its associated risk factors: A survey of electronics manufacturing shift workers in Malaysia - Mohd Shahril, Abu Hanifah; Norazura, Ismail (Taylor & Francis, 2020)
Background: Fatigue among shift workers is one of the problems that not only can cause health impairment but also lead to decrement in safety performance. In Malaysia, few studies have been conducted on the prevalence of fatigue and its risk factors among shift workers, especially in the electronics manufacturing industries when compared with other countries.